2013
DOI: 10.1177/1090198113515244
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Parental Acceptance of the H1N1 Vaccine

Abstract: Although designated as a high-risk group during the 2009-2010 H1N1 pandemic, only about 40% of U.S. children received the vaccine, a relatively low percentage compared with high-risk groups in seasonal influenza, such as the elderly, whose vaccine rates typically top 70%. To better understand parental decision making and predictors of acceptance of the H1N1 vaccine, we examined data from a representative national sample of parents (n = 684), using the health belief model as a framework. The most important pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…For childhood vaccination, the current observed relationships between perceived risk and child vaccination are consistent with Rubin and colleagues’ Rubin et al [31] finding that perceived risk mediated their observed relationship between National Health Service (NHS) work and likely vaccine uptake [31] . However, this relationship between perceived risk and parental H1N1 vaccine uptake was not observed in a recent paper from the United States ( [16] ; but cf. [26] 3 ; [34] ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For childhood vaccination, the current observed relationships between perceived risk and child vaccination are consistent with Rubin and colleagues’ Rubin et al [31] finding that perceived risk mediated their observed relationship between National Health Service (NHS) work and likely vaccine uptake [31] . However, this relationship between perceived risk and parental H1N1 vaccine uptake was not observed in a recent paper from the United States ( [16] ; but cf. [26] 3 ; [34] ).…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, a further examination of Bish and colleagues’ systematic review reveals only four studies (including [31] ) that specifically focused on parental vaccination behaviour (Setbon and Raude, 2010; Schwarzinger et al, 2010; Torun and Torun, 2010; cited in Bish et al [2] ). Although there is a broader literature concerning predictors of parental vaccination during H1N1 (e.g., [4] , [5] , [9] , [16] , [18] , [26] , [34] ; see also Larson, Jarrett, Eckersberger, Smith, & Paterson for a broader systematic review of childhood vaccine hesitancy), we are unaware of any additional quantitative papers concerning predictors of UK parental vaccination during the H1N1 pandemic. Given the threat posed by a future influenza pandemic and the low uptake of vaccination in the prior pandemic (particularly among young children), further understanding of vaccine uptake among all ages of the UK general population during the H1N1 pandemic is critical.…”
Section: Introductionmentioning
confidence: 99%
“…6 articles found that lacking perceived behavioral control was a significant barrier to vaccine uptake (Public 5/191 [ 124 , 155 , 199 , 200 , 220 ]; Unspecified 1/22 [ 221 ]); as was low self-efficacy (HCP 1/117 [ 153 ]; Elderly 1/62 [ 222 ]; Children 1/18 [ 223 ]; Public 5/191 [ 124 , 209 , 210 , 224 , 225 ]). For example, a study by Hilyard et al found that “parents were 1.3 times more likely than others to get their children vaccinated for every standard deviation increase in self-efficacy” [ 226 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding may provide support for the importance of social norms in encouraging vaccination among parents as other studies have demonstrated. [23][24][25][26][27][28][29][30] Second, we can say that media exposure may contribute to a positive attitude of parents which was associated with their adolescent receiving an influenza vaccine. A previous study found a relationship between media exposure and knowledge about vaccines, 13,23 but none have examined the relationship between sources of information about influenza vaccine and parental attitudes and how this may impact influenza vaccination uptake.…”
Section: Discussionmentioning
confidence: 99%